Making archives in early modern Europe : proof, information and political record-keeping, 1400-1700 - Head, Randolph Conrad (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2019)
European states were overwhelmed with information around 1500. Their agents sought to organize their overflowing archives to provide trustworthy evidence and comprehensive knowledge that was useful in the everyday exercise of power. This detailed comparative study explores cases from Lisbon to Vienna to Berlin in order to understand how changing information technologies and ambitious programs of state-building challenged record-keepers to find new ways to organize and access the information in their archives. From the intriguing details of how clerks invented new ways to index and catalog the expanding world to the evolution of new perspectives on knowledge and power among philologists and historians, this book provides illuminating vignettes and revealing comparisons about a core technology of governance in early modern Europe. Enhanced by perspectives from the history of knowledge and from archival science, this wide-ranging study explores the potential and the limitations of knowledge management as media technologies evolved.
Introduction: Records, tools and archives in Europe to 1700 -- Archival history: Literature and outlook -- PART I: The Work of Records (1200- ) -- Probative objects and Scholastic tools in the High Middle Ages -- A late medieval chancellery and its books: Lisbon, 1460-1560 -- Keeping and organizing information from the Middle Ages to the 16th Century -- Information management in early modern Innsbruck, 1490-1530 -- Part II: The Challenges of Accumulation (1400- ) -- The accumulation of records and the evolution of inventories -- Early modern inventories: Habsburg Austria and Würzburg -- Classification: The architecture of knowledge and the placement of records -- The formal logic of classification: Topography and taxonomy in Swiss urban records, 1500-1700 -- Part III: Comprehensive visions and differentiating practices (1550- ) -- Evolving expectations about archives, 1540-1650 -- Registries: Tracking the business of governance -- Part IV: Rethinking records and state archives (1550- ) -- Understanding records: New perspectives and new readings after 1550 -- New disciplines of authenticity and authority: Mabillon's diplomatics and the ius archivi -- Conclusion: The era of chancellery books and beyond.
Includes bibliographical references and index.
Description based on print version record.
eBooks on EBSCOhost
Keywords: Archives -- Europe -- History -- To 1500.; Archives -- Europe -- History -- 16th century; Archives -- Europe -- History -- 17th century; Archival resources -- Europe -- History -- To 1500.; Archival resources -- Europe -- History -- 16th century; Archival resources -- Europe -- History -- 17th century; Archives -- Europe -- Histoire -- Jusqu'à 1500.; Archives -- Europe -- Histoire -- 16e siècle.; Archives -- Europe -- Histoire -- 17e siècle.; Fonds d'archives -- Europe -- Histoire -- 16e siècle.; Fonds d'archives -- Europe -- Histoire -- 17e siècle.; Archival resources; Archives; Europe; To 1699; History